Therapeutic value of conization in cervical carcinoma and dysplasias incipient - Castellano, Carlos (2015)
283 cases of carcinoma in situ of the cervix are investigated to establish the value of conization in its diagnosis and treatment. Conization in this series, constitutes the best procedure for diagnosis of invasive lesions and should be preferently used as a guide to the individual treatment. Hysterectomy without previous conization as practised in 27 cases is held as a risk to the patient while the conservative approach with conization alone followed by adequate control renders excellent therapeutic results. However, hysterectomy extended to vagina remains the procedure of choice.